Resilience of Army Soldiers Who are Carrying Out Operational Tasks in the Papua Region - Negara, Deliyana Yudha; Abidin, Zainal; Hanam, Yuliana (Universitas Muhammadiyah Metro, 2024)
As an Indonesian army, carrying out operational duties in Papua will experience obstacles from internal and external sources, making the operational duties more challenging. By having good resilience, Indonesian armies carrying out operational tasks in Papua can overcome obstacles and meet the expectations of the leadership and the soldiers. Resilience is an individual's ability to respond to adversity or trauma in healthy and productive ways. This study aims to explore and understand the resilience abilities of the Indonesian army, which is carrying out operational tasks in the Papua. The research was conducted using a qualitative approach with a generic qualitative design. Participants consisted of 3 Army soldiers with different ranks on duty in Papua. Data collection was conducted through online semi-structured interviews. The results showed that the factors that influence soldiers' resilience include: 1) External support; 2) Concerns for the safety of self and others; 3) Efforts to overcome obstacles; 4) Duties and responsibilities; 5) Obstacles encountered; and 6) Closeness between personnel. In conclusion, soldiers can survive and adapt to various difficulties in Papua due to external support and efforts made in carrying out duties and responsibilities.